Literasi Informasi Digital : Sebuah Tantangan bagi Pustakawan - Daryono Daryono (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2017)
Information literacy, in addition to being seen as a set of interpersonal competencies, can also be understood from the standpoint of society and human rights. The creativity of librarians in developing and improving services in the digital age is needed to pay attention. Librarians are able to take an active role in taking part in today's emerging technology era by innovating in services. In this era of technology and digital become the trend with slogan "world in our grip" so that library can no longer only build physical facilities and services which are conventional ones, but they have to be developed according to the development of time. Any intensive communication with users is an attempt to find out how digital information literacy is used and how library information literacy services can be integrated to the digital lifestyle of the users. In the world of librarianship the facts mentioned above are more appropriate if they are viewed in the context of digital information literacy that have been parts of the program in many libraries. However, it is necessary to extend the scope considering that digital phenomena are basically related to the use of media and communal capital in everyday life.